KEBEBASAN AKADEMIK DAN OTONOMI KEILMUAN DALAM SISTEM PEMERINTAHAN DEMOKRASI PANCASILA (Studi Kasus Webinar Constitutional Law Society Fakultas Hukum Universitas Gadjah Mada Yogyakarta) - Delpedro Marhaen Rismansyah; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2022)
Academic freedom and scientific autonomy are rights held by students and professors, butacademic freedom and scientific autonomy often experience problems such as those in thewebinar Case Study, "Academic Freedom and Scientific Autonomy in the PancasilaDemocratic Government System (the Constitutional Law Sociétional webinar Case Study."TheFaculty of Law of Gadjah Mada University Yogyakarta)". Is the webinar on "The Problem ofPresidential Dismissal in the midst of Pandemic Review of the State System" at Gadjah MadaUniversity Yogyakarta justified to be held in Indonesia that practices the Pancasilademocratic government system? Research results showed that the "Problem of PresidentialDismissal in the midst of Pandemic Review of the State System" at Gadjah Mada UniversityYogyakarta was legally justified to be held in Indonesia which practiced Pancasila'sdemocratic government system, as it did not conflict with Article 28 of 1945 and regulations.legislation on academic freedom and scientific autonomy. The actions of some unknownindividuals who terrorized the webinar organizers were against the law, contrary toPancasila's democracy and violated human rights to free speech, opinion, and gatherings andto violate the academic freedom and autonomy of science stipulated in the 1945 Constitutionand the laws of law.